Formal consensus to identify clinically important changes in management resulting from the use of cardiovascular magnetic resonance (CMR) in patients who activate the primary percutaneous coronary intervention (PPCI) pathway. Issue 6 (22nd June 2017) - Pufulete, Maria; Brierley, Rachel C; Bucciarelli-Ducci, Chiara; Greenwood, John P; Dorman, Stephen; Anderson, Richard A; Harris, Jessica; McAlindon, Elisa; Rogers, Chris A; Reeves, Barnaby C
Abstract : Objective: To define important changes in management arising from the use of cardiovascular magnetic resonance (CMR) in patients who activate the primary percutaneous coronary intervention (PPCI) pathway. Design: Formal consensus study using literature review and cardiologist expert opinion to formulate consensus statements and setting up a consensus panel to review the statements (by completing a web-based survey, attending a face-to-face meeting to discuss survey results and modify the survey to reflect group discussion and completing the modified survey to determine which statements were in consensus). Participants: Formulation of consensus statements: four cardiologists (two CMR and two interventional) and six non-clinical researchers. Formal consensus: seven cardiologists (two CMR and three interventional, one echocardiography and one heart failure). Forty-nine additional cardiologists completed the modified survey. Results: Thirty-seven draft statements describing changes in management following CMR were generated; these were condensed into 12 statements and reviewed through the formal consensus process. Three of 12 statements were classified in consensus in the first survey; these related to the role of CMR in identifying the cause of out-of-hospital cardiac arrest, providing a definitive diagnosis in patients found to have unobstructed arteries on angiography and identifying patients with left ventricular thrombus. Two additional statements were in consensus in the modified survey, relating to the ability of CMR to identify patients who have a poor prognosis after PPCI and assess ischaemia and viability in patients with multivessel disease. Conclusion: There was consensus that CMR leads to clinically important changes in management in five subgroups of patients who activate the PPCI pathway.